Attitude Towards Documentation and Its Associated Factors Among Nurses Working in Public Hospitals of Hawassa City Administration, Southern Ethiopia - Sisay Ayele BSc, MSc; Tesfaye Gobena BSc, MPH, PhD; Simon Birhanu BSc, MPH; Tesfaye Assebe Yadeta BSc, MSc, PhD (SAGE Publishing, 2021)
Background Nursing documentation is the record of nursing care that has been planned and delivered to individual clients by qualified nurses or under the direction of qualified nurses. Various studies have shown that documentation is still a critical issue in both high- and low-income countries, especially in Sub-Saharan Africa like Ethiopia. However, there is a paucity of data in Ethiopia, the attitude of nurses towards nursing care documentation, particularly in the study setting. Therefore, this study aimed to assess the nurse's attitude towards documentation and associated factors in Hawassa City administration public hospitals, Southern Ethiopia. Methods Institutional based cross-sectional study was conducted among 422 nurses from March 01 to 30, 2020. A simple random sampling technique was applied to select the study participants. Data were collected using a self-administered questionnaire. Statistical package of social science (SPSS) version 20.0 software was used for analysis. The association between the attitude of nurses towards documentation and predictors was determined using multivariable logistic regression analysis. The level of statistical significance was determined at a p-value of less than 0.05. Result Among 413 nurses who participated in the study, 58.8% [95% CI of 54.5% to 63.7%] of them had a favorable attitude towards documentation. Work setting [AOR = 1.94 (95% CI: 1.23-3.05)] and Knowledge [AOR = 3.28 (95% CI: 2.08-5.16)], were significantly associated factors with nurses' attitude towards documentation. Conclusion and Recommendations: More than half of the study participants had a favorable attitude towards documentation. Working unit and knowledge were factors associated with nurse's attitude toward nursing care documentation. Therefore, increasing nurse's knowledge about documentation and managing working units effectively are recommended to increase the nurses' attitude toward documentation.